2014
DOI: 10.5430/afr.v3n4p24
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Asset Pricing Models in the Egyptian Stock Market

Abstract: This paper employs GRS test to empirically compare the applicability of five alternatives of asset pricing models for 55 shares listed on the EGX100 for the Egyptian stock market: 1) the CAPM, 2) the Fama-French three factor model, 3) the Cahart four factor model, 4) liquidity-augmented four factor model, 5) and the five factor model (liquidity and momentum-augmented Fama-French three factor model. The sample is split into six portfolios sorted on size and book-to market ratio and 45 shares are excluded due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…The findings of the study show the significant negative impact of firm size on stock return. This result is consistent with the findings of Banz (1981), Wong, Tan and Liu (2006), Kumar and Sehgal (2004) and Shaker and Elgiziry (2014) Similarly, book to market equity and earning yield also have significant negative impact on stock return in Nepalese context. However, this finding contradicts with the findings of Lakonishok (1991), Stattman (1980), Rosenberg, Basu (1983), and Ball (1978).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of the study show the significant negative impact of firm size on stock return. This result is consistent with the findings of Banz (1981), Wong, Tan and Liu (2006), Kumar and Sehgal (2004) and Shaker and Elgiziry (2014) Similarly, book to market equity and earning yield also have significant negative impact on stock return in Nepalese context. However, this finding contradicts with the findings of Lakonishok (1991), Stattman (1980), Rosenberg, Basu (1983), and Ball (1978).…”
Section: Discussionsupporting
confidence: 91%
“…Banz (1981) reported that smaller firms have had higher risk-adjusted returns on average, than larger firms. Likewise, Fama and French (1992), Kumar and Sehgal (2004), Wong, Tan and Liu (2006) and Shaker and Elgiziry (2014) also reported similar findings. In contrast, Hassan and Javed (2011) and Acheampong, Agalega, and Shibu (2014) found that size has the significant positive impact on stock return; while Davis in 1994 had noted positive but insignificant impact of size on stock return.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…However, despite this criticism, Shaker and Elgiziry (2014) test the Fama and French three-factor model in the Egyptian stock market by using six portfolios double-sorted on size and book-to-market ratio as the main test assets. Their results show that the Fama and French model is the best asset pricing model for the Egyptian stock market as it outperforms other models (Note 1) in explaining stock returns.…”
Section: The Fama and French Three-factor Modelmentioning
confidence: 99%
“…This showed that the Five Factor explained more variation than the CAPM in Australian market. In their study of a comparison of asset pricing models in the Egyptian Stock Market, Shaker and Elgiziry (2014), also found that the Five Factor explained more variation than the CAPM.…”
Section: Literature Reviewmentioning
confidence: 99%